Crescimento inicial de Bauhinia forficata Link. e Maytenus ilicifolia Mart. ex Reissek produzidas com insumos biológicos - Peccatti, Aline (2017)
The present study aimed to evaluate the potential of the biological inputs Trichoderma spp. and bovine vermicompost in the initial growth of the species Bauhinia forficata and Maytenus ilicifolia, aiming the development of alternative techniques for the production of seedlings of medicinal species. The essays were conducted at the Fundação Estadual de Pesquisa Agropecuária in Santa Maria, RS. Was used an entirely casualized experimental design with 40 replicates for each species. Different fungal isolates (Tricho 1, Tricho 2, Tricho 13, Tricho 33 and Tricho 10) of the genus Trichoderma were inoculated on MecPlant® and Carolina Soil® substrates constituting the treatments tested in the two tests for the production of B. forficata and M. ilicifolia respectively. For the production of B. forficata and M. ilicifolia with vermicompost, different proportions of bovine vermicompost (0, 20, 40, 50, 60 and 80%) and non-sterile soil were tested. The variables height, collar diameter and leaf number of the seedlings were evaluated at 45, 90 and 135 days for B. forficata and at 90, 120, 150 and 180 days after seeding for M. ilicifolia. For B. forficata the chlorophyll content was also evaluated in the three seasons, survival, leaf area, total dry mass, aerial and radicular, dry biomass ratio of shoot and radicular, and Dickson Quality Index at 135 days. The survival of M. ilicifolia seedlings was performed at 180 days. The Kruskal-Wallis test (α=0,05) was used to compare the mean values, considering the assumptions of normality and homogeneity of the variances were not observed, except for the B. forficata leaf area that was submitted to the Tukey test (α=0,05). The use of the biological inputs Trichoderma spp. and vermicompost were efficient to promote the initial growth of Bauhinia forficata under greenhouse conditions. The variables that best expressed this effect, for both inputs, were height and collar diameter from the 90 days and leaf area. In general, the Tricho 13 isolate proved to be more efficient than the other isolates tested. There was a tendency for treatments with higher vermicompost proportions (50, 60 and 80%) to present better results in the studied variables, due to improvements in the physical-chemical and biological characteristics of the substrate. In relation to M. ilicifolia, the use of the Trichoderma spp. and vermicompost inputs showed different responses in the production of seedlings. Trichoderma spp. inoculation on the substrate did not promote seedling growth. It is believed that some kind of negative interaction occurred between M. ilicifolia and Trichoderma spp. during the germination process. The use of the vermicompost proportions (20, 40, 50 and 60%) promoted the growth of the plants, however, it was verified that the slow growth of the species associated to the higher volume of vermicompost with a proportion of 80% implied in substrate losses.